At First Glance: Psoriatic Response to Transdermal Nicotine Patch Application - Joseph M. LaRochelle; Victoria R. Dimitriades (MDPI AG, 2020)
Contact dermatitis and psoriasis are common skin disorders which represent two distinct pathologies. Skin disorders heavily rely on corresponding history for diagnosis; this case demonstrates the challenges of relying on history alone for final identification. A patient presented to clinic for evaluation of a new rash on his abdomen. Past medical history was notable for recent initiation of a smoking cessation program utilizing nicotine patches as well as a pharyngitis treated with antibiotics 1 week prior. Despite use of topical steroid and cessation of the patches, the well-demarcated rash became more generalized. Patch testing for the nicotine patch and chemical sensitizers was negative and an eventual biopsy was consistent with guttate psoriasis. Contact dermatitis relies heavily on clinical history for diagnosis. This case demonstrates that history can be misleading. In retrospect, it is likely that a preceding presumed streptococcal infection was the primary inducer of guttate psoriasis.